Silica composite microparticles comprising nanostructures

By directly embedding the silica particles of the nanostructured bodies in the display device, the problem of increasing cost and complexity of the barrier layer is solved, and the stability and photoluminescence efficiency are improved, and the manufacturing process is simplified.

CN119173609APending Publication Date: 2024-12-20SHOEI CHEM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-25
Filing Date
2023-03-24
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Current quantum dot reinforced membranes (QDEFs) require barrier layers to provide stability, but barrier layers increase cost and complexity, and lack effective nanostructure compositions to improve stability.

Method used

Using a method without barrier layer, silica particles containing nanostructures are embedded into an optical grade polymer film by extrusion or similar process, and nanocrystal core and shell compositions, such as InP, CdSe, ZnSe, etc., are formed. Stable nanostructures, directly used in display devices.

Benefits of technology

Reduces device costs, improves the stability and photoluminescence efficiency of nanostructures, and does not require additional barrier protection, simplifying the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173609A_ABST
    Figure CN119173609A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of nanostructures. Provided herein are microparticles comprising a nanostructure and silica. Also provided herein are methods of making the microparticles, films comprising the microparticles, and devices comprising the microparticles. Also provided herein are display backlight units (BLUs) that do not include a barrier layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nanostructures. Silica composite particles containing nanostructures are provided. Methods for preparing the particles, films containing the particles, and devices containing the particles are also provided. A display backlight unit (BLU) without a barrier layer is also provided. Background Art

[0002] Quantum dot enhanced film (QDEF) is a multilayer structure consisting of nanostructures embedded in a polymer resin sandwiched between one or more barrier layers. The barrier layers provide stability in operating conditions such as flux, temperature and humidity. However, the barrier layers impose additional costs on the product.

[0003] There is a need for films comprising nanostructure compositions having improved stability without the need for a barrier layer. Summary of the invention

[0004] A unique method is provided to provide a QDEF film that does not require a barrier layer and contains silica particles containing nanostructures. The silica particles containing nanostructures can be embedded in any optical grade polymer film by extrusion or similar processes, and the film can be used as a QDEF in display devices. Because the particles are stable and do not require a barrier layer, the cost of the device containing the particles is reduced. In some embodiments, the QDEF is Figure 1 Displayed in.

[0005] The present disclosure provides compositions comprising a population of nanostructures comprising nanocrystalline cores, wherein the nanostructures are embedded in silica microparticles.

[0006] In some embodiments, the nanocrystalline core is selected from Si, Ge, Sn, Se, Te, B, C, P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, Ag1nGaS, and combinations thereof.

[0007] In some embodiments, the nanocrystal core comprises InP.

[0008] In some embodiments, the nanocrystal core comprises CdSe.

[0009] In some embodiments, the nanocrystalline core comprises at least one shell.

[0010] In some embodiments, the at least one shell is ZnSe.

[0011] In some embodiments, the at least one shell is ZnS.

[0012] In some embodiments, the nanostructure comprises silver, indium, gallium, and sulfur (AIGS).

[0013] In some embodiments, the silicate particles have a diameter of about 1 μm to about 20 μm.

[0014] In some embodiments, the silica particles have an average particle size of about 2 μm to about 12 μm.

[0015] The present disclosure also provides a method of making a composition described herein, the method comprising:

[0016] (a) mixing the nanostructure and the metal or ammonium silicate in water;

[0017] (b) adding the blend obtained in (a) to a solution comprising a nonionic surfactant in a nonpolar aprotic solvent and mixing to obtain a first microemulsion;

[0018] (c) removing water from the first microemulsion obtained in (b);

[0019] (d) mixing acetic acid, a nonionic surfactant, and a nonpolar aprotic solvent to obtain a second microemulsion;

[0020] (e) blending the first and second microemulsions to obtain silica particles containing the nanostructures; and

[0021] (f) isolating the microparticles obtained in (e).

[0022] In some embodiments, the first and second microemulsions are passed through a filter having pores less than 10 μm prior to blending in (e).

[0023] In some embodiments, the non-polar aprotic solvent comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, or squalane, or a combination thereof.

[0024] In some embodiments, the non-polar aprotic solvent comprises 1-octadecene.

[0025] The present disclosure also provides a nanostructure film comprising:

[0026] (a) a composition as described herein; and

[0027] (b) at least one organic resin.

[0028] In some embodiments, the microparticles are embedded in at least one organic resin forming the film.

[0029] In some embodiments, the film is cured.

[0030] In some embodiments, the film is formed by extrusion.

[0031] In some embodiments, the film does not include a barrier layer having low oxygen and moisture permeability adjacent to the film.

[0032] The present disclosure also provides nanostructure molded articles comprising:

[0033] (a) a first conductive layer;

[0034] (b) a second conductive layer; and

[0035] (c) a nanostructure layer between the first conductive layer and the second conductive layer, wherein the nanostructure layer comprises a composition described herein.

[0036] In some embodiments, the nanostructure molded article does not include a barrier layer having low oxygen and moisture permeability adjacent to the film.

[0037] The present disclosure also provides display devices comprising the compositions described herein.

[0038] In some embodiments, the microparticles are embedded in a matrix forming a film within the display device.

[0039] In some embodiments, the film is disposed on a light guide plate.

[0040] In some embodiments, the display device does not include a barrier layer having low oxygen and moisture permeability adjacent to the film.

[0041] The present disclosure also provides a display backlight unit (BLU) comprising:

[0042] (a) at least one primary light source emitting primary light;

[0043] (b) a light guide plate (LGP) optically coupled to the at least one primary light source, whereby the primary light is uniformly transmitted through the LG; and

[0044] (c) an extruded film disposed on the LGP, wherein the primary light is uniformly transmitted through the LGP and into the extruded film;

[0045] (d) wherein the extruded film is not directly physically coupled to the LGP and comprises one or more populations of nanostructures configured to emit secondary light, wherein at least a portion of the primary light is absorbed by the nanostructures and re-emitted by the nanostructures as the secondary light, and wherein the BLU does not comprise a barrier layer.

[0046] In some embodiments, the nanostructure comprises a nanocrystalline core selected from the group consisting of Si, Ge, Sn, Se, Te, B, C, P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, Ag1nGaS, and combinations thereof.

[0047] In some embodiments, the nanocrystal core comprises InP.

[0048] In some embodiments, the nanocrystal core comprises CdSe.

[0049] In some embodiments, the nanocrystalline core comprises at least one shell.

[0050] In some embodiments, the at least one shell is ZnSe.

[0051] In some embodiments, the at least one shell is ZnS.

[0052] In some embodiments, the nanostructure comprises silver, indium, gallium, and sulfur (AIGS).

[0053] In some embodiments, the extruded film comprises at least one organic resin.

[0054] In some embodiments, the at least one organic resin is poly(methyl methacrylate) (PMMA), polyethylene terephthalate (PET), or a combination thereof.

[0055] In some embodiments, the one or more populations of nanostructures are encapsulated by an inorganic material.

[0056] In some embodiments, the inorganic material comprises silica particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] The accompanying drawings, which are incorporated herein and form a part of the specification, illustrate the present invention and, together with the description, further serve to explain the principles of the invention and enable those skilled in the relevant art to make and use the invention.

[0058] Figure 1 To depict a schematic diagram of an extruded polymer film 101 having embedded silica particles 102 containing nanostructures 103 .

[0059] Figure 2 FIG. 1 is a process flow chart for the synthesis of calcium silicate particles containing nanostructures.

[0060] Figures 3A-3C The scanning electron microscope (SEM) images of calcium silicate particles containing nanostructures at different magnifications.

[0061] Figure 4 To display from Figures 3A-3C Graph of the particle size distribution of calcium silicate particles containing nanostructures.

[0062] Figures 5A-5D To show the results of the experiments at 50°C under high throughput (1, 10 and 68X, Figure 5A ), under accelerated conditions at 80 °C at high throughput ( Figure 5B ), stored at 85°C in the dark (dark storage) ( Figure 5C ), and a graph of the emission power of a quantum dot enhanced film (QDEF) stored at 60°C and 90% relative humidity.

[0063] Figure 6 FIG. 1 is a process flow chart for the synthesis of calcium silicate particles containing nanostructures.

[0064] Figure 7A-7B SEM images and particle size distribution of calcium silicate particles containing nanostructures at different magnifications ( Figure 7C ).

[0065] Figure 8 The process flow chart of the synthesis of silica particles containing nanostructures.

[0066] Figures 9A-9C The SEM images and particle size distribution of silica particles containing nanostructures at different magnifications ( Fig.9D ).

[0067] Figures 10A-10C The SEM images and particle size distribution of silica particles containing nanostructures at different magnifications ( Fig. 10D ).

[0068] Figures 11A-11C is a SEM image of a cross section of an extruded polymethylmethacrylate (PMMA) film containing silica particles containing nanostructures, showing the distribution and stability of the particles after the extrusion process.

[0069] Figures 12A-12D To show that at 85°C, stored in the dark ( Fig. 12A ), at 1&10X flux at 50°C ( Fig. 12B ), stored at 60°C / 90% relative humidity ( Fig. 12C ), and a graph of the emission power of a quantum dot enhanced film (QDEF) at 80°C at 1 & 10X flux.

[0070] Fig.13 FIG. 1 is a process flow chart for the synthesis of calcium silicate particles containing nanostructures.

[0071] Figures 14A-14C SEM images and particle size distribution of calcium silicate particles containing nanostructures at different magnifications ( Fig.14D ).

[0072] Figures 15A-15D To show the QDEF at 50°C at 1, 10 & 68X flux ( Fig.15A ), at 1 & 10X flux at 80°C ( Fig. 15B ), stored in dark place at 85℃ ( Fig. 15C ), and storage at 60°C / 90% relative humidity ( Fig.15D )’s QDEF transmission power.

[0073] Figures 16A-16B is a SEM image of silica particles containing nanostructures obtained by the reaction of ammonium silicate with acetic acid as described in Example 4. Fig. 16C The table showing the chemical composition of the silica particles shows that they are composed of CdS / ZnSe nanostructures and silica.

[0074] Figures 17A-17B : is a SEM image of silica particles containing nanostructures obtained by the emulsion process described in Example 2. Fig. 17C Table showing the presence of silicon, calcium, cadmium, zinc, sulfur and selenium in the silica microparticles, showing that it consists of CdS / ZnSe nanostructures and calcium silicate.

[0075] Figures 18A-18B is a SEM image of silica microparticles containing nanostructures obtained by the emulsion process described in Example 2 using a lithium silicate starting material. Fig. 18C Table showing the chemical composition of silicate particles showing that they consist of CdS / ZnSe nanostructures and calcium silicate. DETAILED DESCRIPTION

[0076] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. The following definitions supplement those in the art and are for the current application, and should not be imputed to any related or unrelated cases, for example, any jointly owned patents or applications. Although any methods and materials similar or equivalent to those described herein can be used for testing in practice, preferred materials and methods are described herein. Accordingly, the terms used herein are only used for the purpose of describing specific embodiments, and are not intended to be restrictive.

[0077] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a nanostructure" includes a plurality of such nanostructures, and the like.

[0078] As used herein, the term "about" indicates that a given amount varies by ±10% of the stated value. For example, "about 100 nm" encompasses a size range from 90 nm to 110 nm, inclusive.

[0079] "Nanostructure" is a structure having at least one region or characteristic size (dimension, dimension) having a size less than about 500nm. In some embodiments, the nanostructure has a size less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm such as 1-10nm. Typically, the region or characteristic size will be along the minimum axis of the structure. The example of such structure includes nanowire, nanorod, nanotube, branched nanostructure, nano tetrapod, tripod, dipod, nanocrystal, nano dot, quantum dot, nanoparticle, etc. The nanostructure can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous or its combination. In some embodiments, the three sizes of the nanostructure each have a size less than about 500nm, less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.

[0080] When used with respect to a nanostructure, the term "heterostructure" refers to a nanostructure characterized by at least two different and / or distinguishable material types. Typically, one region of a nanostructure comprises a first material type, while a second region of the nanostructure comprises a second material type. In some embodiments, a nanostructure comprises a core of a first material and at least one shell of a second (or third, etc.) material, wherein the different material types are radially distributed around, for example, the long axis of a nanowire, the long axis of an arm of a branched nanowire, or the center of a nanocrystal. A shell may, but need not, completely cover an adjacent material to be considered a shell, or be considered a heterostructure for a nanostructure; for example, a nanocrystal characterized by a core of a material being covered by an island of a second material is a heterostructure. In other embodiments, different material types are distributed at different locations within a nanostructure; for example, along the long axis of a nanowire or along the long axis of an arm of a branched nanowire. Different regions within a heterostructure may comprise completely different materials, or the different regions may comprise a base material (e.g., silicon) having different dopants or different concentrations of the same dopant.

[0081] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross section orthogonal to the first axis of the nanostructure, wherein the first axis has the largest difference in length relative to the second and third axes (the second and third axes being two axes whose lengths are most nearly equal to each other). The first axis is not necessarily the longest axis of the nanostructure; for example, for a disc-shaped nanostructure, the cross section will be a substantially circular cross section orthogonal to the short longitudinal axis of the disc. If the cross section is not circular, the diameter is the average value of the major axis and the minor axis of the cross section. For extended or high aspect ratio nanostructures such as nanowires, the diameter is measured on a cross section perpendicular to the longest axis of the nanowire. For a spherical nanostructure, the diameter is measured from one side through the center of the sphere to the other side.

[0082] When used about nanostructure, the term "crystalline" or "substantially crystalline" refers to the fact that nanostructure typically exhibits long-range order on one or more dimensions of the structure. It will be appreciated by those skilled in the art that the term "long-range order" will depend on the absolute size of the specific nanostructure, because the order of a single crystal cannot extend beyond the boundaries of the crystal. In this case, "long-range order" will mean substantially ordered along at least most dimensions of the nanostructure. In some cases, the nanostructure may be provided with an oxide or other coating, or may be composed of a core and at least one shell. In such a case, it will be appreciated that the oxide, (one or more) shell or other coating may but need not exhibit such order (for example, it may be amorphous, polycrystalline or other). In such a case, the phrase "crystalline", "substantially crystalline", "substantially monocrystalline" or "monocrystalline" refers to the central core (not including coating or shell) of the nanostructure. The term "crystalline" or "substantially crystalline" as used herein is intended to also encompass structures comprising various defects, stacking faults, atomic substitutions, etc., as long as the structure exhibits substantially long-range order (e.g., order over at least about 80% of the length of at least one axis of the nanostructure or its core). In addition, it will be understood that the interface between the core and the outside of the nanostructure, or between the core and the adjacent shell, or between the shell and the second adjacent shell may contain non-crystalline regions and may even be amorphous. This does not prevent the nanostructure from being crystalline or substantially crystalline as defined herein.

[0083] When used with respect to a nanostructure, the term "monocrystalline" indicates that the nanostructure is substantially crystalline and substantially comprises a single crystal. When used with respect to a nanostructure heterostructure comprising a core and one or more shells, "monocrystalline" indicates that the core is substantially crystalline and substantially comprises a single crystal.

[0084] "Nanocrystal" is a nanostructure of monocrystal basically.Therefore, nanocrystal has at least one region or characteristic size having a size less than about 500nm.In some embodiments, the nanocrystal has a size less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm, for example, 1-10nm.The term "nanocrystal" is intended to encompass the nanostructure of monocrystal basically comprising various defects, stacking faults, atomic substitutions, etc., and the nanostructure of monocrystal basically without such defects, stacking faults or substitutions.In the case of the nanocrystal heterogeneous structure comprising core and one or more shells, the core of the nanocrystal is typically monocrystalline basically, but (one or more) shells do not need to be.In some embodiments, the three dimensions of the nanocrystal have a size less than about 500nm, less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm respectively.

[0085] The term "quantum dot" (or "dot") refers to a nanocrystal that exhibits quantum confinement or exciton confinement. Quantum dots may be substantially homogeneous (uniform) in terms of material properties, or in some embodiments may be heterogeneous, e.g., comprising a core and at least one shell. The optical properties of quantum dots may be affected by their particle size, chemical composition, and / or surface composition, and may be determined by suitable optical tests available in the art. The ability to customize nanocrystal size, e.g., in the range of about 1 nm and about 15 nm, enables photoemission coverage across the entire spectrum to provide great versatility in color rendering.

[0086] A "ligand" is a molecule capable of interacting (whether weakly or strongly) with one or more faces of a nanostructure, for example, through covalent, ionic, van der Waals forces, or other molecular interactions with the surface of the nanostructure.

[0087] "Photoluminescence quantum yield" (PLQY) is the ratio of photons emitted to photons absorbed, for example, by a nanostructure or population of nanostructures. As known in the art, quantum yield is typically determined by comparative methods using well-characterized standard samples with known quantum yield values.

[0088] "Peak emission wavelength" (PWL) is the wavelength where the radiation emission spectrum of a light source reaches its maximum.

[0089] As used in this article, the term "shell" refers to the material deposited on the core or on a previously deposited shell of the same or different composition and derived from a single deposition behavior of the shell material. Exact shell thickness depends on material and precursor input and conversion, and can be reported as nanometer or monolayer. As used in this article, "target shell thickness" refers to the shell thickness of the expectation of the precursor amount required for calculation. As used in this article, "actual shell thickness" refers to the amount of the actual deposition of the shell material after synthesis, and can be measured by methods known in the art. For example, actual shell thickness can be measured by comparing the particle diameter determined from the transmission electron microscope (TEM) image of nanocrystal before and after the shell is synthesized.

[0090] As used herein, the term "full width at half maximum" (FWHM) is a measure of the size distribution of nanoparticles. The emission spectrum of nanoparticles generally has the shape of a Gaussian curve. The width of the Gaussian curve is defined as the FWHM and gives an idea of ​​the size distribution of particles. Smaller FWHM corresponds to narrower quantum dot nanocrystal size distribution. FWHM also depends on the peak emission wavelength.

[0091] As used herein, the term "half width at half maximum" (HWHM) is a measure of the size distribution of nanoparticles extracted from a UV-visible spectral curve. The HWHM on the lower energy side of the first exciton absorption peak can be used as a suitable indicator of size distribution, where a smaller HWHM value corresponds to a narrower size distribution.

[0092] As used herein, microparticles are particles with a diameter of 100 μm or less. In some embodiments, microparticles have a diameter of about 1 to about 20 μm. In some embodiments, microparticles have a diameter of about 1 to about 15 μm. In some embodiments, microparticles have a diameter of about 1 to about 12 μm. In some embodiments, microparticles have a diameter of about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, about 10, about 11, about 12, about 13, about 14, about 15, about 16, about 17, about 18, or about 20 μm. In some embodiments, the average microparticle size is about 2 to about 12 μm. In some embodiments, the average microparticle size is about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, about 10, about 11, about 12 μm.

[0093] Microparticle composition

[0094] In some embodiments, the microparticle composition comprises one or more nanostructures and silicon dioxide. In some embodiments, the microparticle composition may further comprise a metal silicate such as lithium silicate or calcium silicate. In other embodiments, the microparticle may comprise ammonium silicate.

[0095] Method for making microparticle composition

[0096] There is provided a method of making a particulate composition comprising calcium silicate as described herein, comprising:

[0097] (a) mixing the nanostructure and metal or ammonium silicate in water;

[0098] (b) adding the blend obtained in (a) to a mixture of a nonpolar aprotic solvent and a nonionic surfactant, and mixing the resulting composition to obtain a first microemulsion;

[0099] (c) filtering the blend obtained in (b);

[0100] (d) removing water from the first microemulsion obtained in (c) to obtain microparticles;

[0101] (e) isolating the microparticles obtained in (d);

[0102] (f) admixing the separated particles obtained in (e) with a calcium halide solution to obtain particles comprising calcium silicate; and

[0103] (g) separating microparticles comprising calcium silicate.

[0104] For example, in (a), 2 mL of an aqueous dispersion of quantum dots (QDs), such as CdSe (9-10 wt % inorganic content) + 3.4 mL of water, is stirred. In some embodiments, the blend further comprises 0.15 ml of (3-mercaptopropyl) trimethoxysilane (MPTMS). In some embodiments, the blending in (a) is performed at room temperature to 100° C. In other embodiments, the blending in (a) is performed at 50-90° C. In other embodiments, the blending in (a) is performed at 50, 55, 60, 65, 70, 75, 80, 85, or 90° C. In some embodiments, the blend is stirred at 80° C. for 5 minutes. Then, a metal silicate solution (e.g., 2.8 mL of a 25 wt % LiSiL solution) is added under good stirring.

[0105] In (b), the nonionic surfactant / nonpolar aprotic solvent mixture is added with good stirring. Examples of nonionic surfactants include 80 (e.g., 1.3 wt % of 16.5 ml) or ). In some embodiments, the non-polar aprotic solvent comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, or squalane, or a combination thereof. The solution becomes milky, indicating the formation of a microemulsion.

[0106] In (c), the blend obtained in (b) is filtered, for example, passed through a micron filter for homogenization. In some embodiments, the filter contains 1-10 μm pores. In some embodiments, the pores are 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 μm in diameter. Homogenization can also be achieved by a mechanical homogenizer.

[0107] In (d), water is removed from the microemulsion by heating and / or placing under reduced pressure. In some embodiments, the microemulsion is heated to 50-100° C. In some embodiments, the microemulsion is heated at 80° C. under vacuum. In some embodiments, the microemulsion is heated at 10 torr vacuum for about 10-15 minutes.

[0108] In (e), the microparticles are separated. In some embodiments, the microparticles are separated, for example, by centrifugation. In some embodiments, the microparticles are separated by centrifugation at 3000-4000 rpm, for example, for 5 minutes.

[0109] In (f), the separated microparticles obtained in (e) are blended with a calcium halide solution to provide microparticles comprising calcium silicate. In some embodiments, the calcium halide is calcium chloride. In some embodiments, the microparticles are dispersed in 7 ml of a 1M calcium chloride solution and stirred at 60°C for 30 minutes.

[0110] In (g), the microparticles containing calcium silicate are separated / purified by washing with a non-solvent. Examples of non-solvents include acetone and ethanol. In some embodiments, the microparticles containing calcium silicate are washed with two acetone washes and two ethanol washes. In some embodiments, the microparticles containing calcium silicate are separated by centrifugation and purified by washing with ethanol (e.g., 2 times).

[0111] In some embodiments, the resulting product is dried to produce a powder and dispersed in a carrier solvent. In some embodiments, the process produces -95% calcium silicate particles per batch with -20 wt% QD loading.

[0112] Also provided are methods of making the silica microparticle compositions described herein, comprising:

[0113] (a) mixing the nanostructure and a metal or ammonium salt in water;

[0114] (b) adding the blend obtained in (a) to a mixture of a nonpolar aprotic solvent and a nonionic surfactant, and mixing the resulting composition to obtain a first microemulsion;

[0115] (c) removing water from the first microemulsion obtained in (b) and separating microparticles;

[0116] (d) blending the microparticles obtained in (c) with acetic acid and a non-polar aprotic solvent to obtain a second microemulsion;

[0117] (e) blending the first and second microemulsions to obtain silica particles containing nanostructures; and

[0118] (f) separating the silica fine particles obtained in (e).

[0119] In some embodiments, the first and second microemulsions are filtered prior to blending in (c). In some embodiments, the first and second microemulsions are passed through a filter having pores of 1-10 μm prior to blending in (e). In some embodiments, the first and second microemulsions are passed through a filter having pores of 5 μm or less prior to blending in (e). In some embodiments, the first and second microemulsions are passed through a filter having pores of 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 μm.

[0120] In some embodiments, the non-polar aprotic solvents used in (b) and (d) are the same or different. In some embodiments, the non-polar aprotic solvent comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, or squalane, or a combination thereof. In (b), examples of non-ionic surfaces include 80 (e.g., 1.3 wt % of 16.5 ml) or ).

[0121] In some embodiments, the blending in (a) is performed at room temperature to 100° C. In other embodiments, the blending in (a) is performed at 50-90° C. In other embodiments, the blending in (a) is performed at 50, 55, 60, 65, 70, 75, 80, 85, or 90° C.

[0122] In some embodiments, the metal silicate is lithium, beryllium, sodium, or potassium silicate. In some embodiments, the ammonium silicate is NH4 + SiO4 = , or single, double, triple or quadruple C 1-4 Alkyl ammonium silicate.

[0123] In (e), the microparticles are separated. In some embodiments, for example, by centrifugation. In some embodiments, the microparticles are separated by centrifugation at 3000-4000 rpm, for example, for 5 minutes.

[0124] In (d), acetic acid and a non-polar aprotic solvent are mixed. In some embodiments, the acetic acid is glacial acetic acid. In other embodiments, the ratio of acetic acid to non-polar aprotic solvent can range from 5% to 95% weight / weight.

[0125] Also provided is a method of making a particulate composition comprising calcium silicate as described herein, comprising:

[0126] 16.5 ml of 3 wt% span 80 / ODE solution was stirred at 600 rpm. 2.8 mL of 25 wt% lithium silicate solution was added with good stirring. The resulting mixture became milky, indicating the formation of a microemulsion.

[0127] The solution was passed through a 6 μm filter for homogenization. This solution was designated "Microemulsion 1".

[0128] 2 mL of QD aqueous dispersion (9-10 wt% inorganic content) + 3.4 mL of water + 0.15 ml of MPTMS were stirred at 60°C for 5 minutes.

[0129] 27.5 ml of 3 wt% span 80 / ODE solution was stirred at 600 rpm. The above QD solution was added dropwise. The resulting mixture became milky, indicating the formation of a microemulsion.

[0130] This solution was also passed through a 6 um filter for homogenization. This solution was called "Microemulsion 2".

[0131] Microemulsions 1 and 2 were mixed and kept under stirring for 30 minutes.

[0132] 15 ml of 3 wt% span 80 / ODE solution was stirred at 600 rpm. 3 ml of 2M calcium chloride solution was added dropwise. The resulting mixture became milky, indicating the formation of a microemulsion.

[0133] The solution was passed through a 6 micron filter for homogenization. This solution was called microemulsion 3.

[0134] Finally, microemulsion 3 was added to the mixture of microemulsions 1 & 2 and the resulting mixture was kept under stirring for 30 minutes for silicate precipitation.

[0135] Finally, the particles are purified by centrifugation and washed with acetone and ethanol. The silica particles containing calcium silicate are then dried and stored in a carrier solvent.

[0136] Nanostructure core

[0137] The nanostructure core used in the present invention can be produced by any suitable material, suitably inorganic material, and more suitably inorganic conductive or semiconductor material. Suitable semiconductor materials include any type of semiconductor, including II-VI, III-V, IV-VI and IV semiconductors. Suitable semiconductor materials include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, Ag1nGaS, and combinations thereof.

[0138] The synthesis of II-VI family nanostructures has been described in U.S. Patent Nos. 6,225,198, 6,322,901, 6,207,229, 6,607,829, 6,861,155, 7,060,243, 7,125,605, 7,374,824, 7,566,476, 8,101,234 and 8,158,193, and in U.S. Patent Application Publication Nos. 2011 / 0262752 and 2011 / 0263062. In some embodiments, the core is a II-VI family nanocrystal selected from ZnO, ZnSe, ZnS, ZnTe, CdO, CdSe, CdS, CdTe, HgO, HgSe, HgS and HgTe. In some embodiments, the core is a nanocrystal selected from ZnSe, ZnS, CdSe and CdS.

[0139] Although II-VI family nanostructures such as CdSe and CdS quantum dots can exhibit desired luminescent behavior, problems such as the toxicity of cadmium limit the applications to which such nanostructures can be used. Therefore, it is highly desirable to have a less toxic alternative with favorable luminescent properties. Conventional III-V family nanostructures and particularly InP-based nanostructures provide the best known alternatives for cadmium-based materials due to their compatible emission ranges.

[0140] The synthesis of InP-based nanostructures has been described in, for example, Xie, R., et al., “Colloidal InP nanocrystals as efficient emitters covering blue to near-infrared”, J. Am. Chem. Soc. 129: 15432-15433 (2007); Micic, O. I., et al., “Core-shell quantum dots of lattice-matched ZnCdSe2 shells on InP cores: Experiment and theory,” J. Phys. Chem. B 104: 12149-12156 (2000); Liu, Z., et al., “Coreduction colloidal synthesis of III-V nanocrystals: The case of InP,” Angew. Chem. Int. Ed. Engl. 47: 3540-3542 (2008); Li, L., et al., “Economic synthesis of high quality InPnanocrystals using calcium phosphide as the phosphorus precursor," Chem. Mater. 20: 2621-2623 (2008); D. Battaglia and X. Peng, "Formation of high quality InP and InAs nanocrystals in a noncoordinating solvent," Nano Letters2:1027-1030(2002); Kim, S. et al., "Highly luminescent InP / GaP / ZnS nanocrystals and their application to white light-emitting diodes," J.Am.Chem.Soc.134:3804-3809(2012); Nann, T., et al., "Water splitting by visible light: Ananophotocathode forhydrogen production," Angew.Chem.Int.Ed.49:1574-1577(2010); Borchert, H., et al., “Investigation of ZnS passivated InP nanocrystals by XPS,” Nano Letters 2:151-154(2002); L. Li and P. Reiss, “One-pot synthesis of highly luminescent InP / ZnS nanocrystals without precursor injection,” J. Am. Chem. Soc. 130:11588-11589(2008); Hussain, S., et al. “One-pot fabrication of high-quality InP / ZnS(core / shell) quantum dots and their application to cellular imaging,” Chemphyschem. 70:1466-1470(2009); Xu, S., et al., “Rapid synthesis of high-quality InP nanocrystals,” J. Am. Chem. Soc. 725:1054-1055(2006); Micic, O. I., et al., “Size-dependent spectroscopy of InP quantum dots,” J. Phys. Chem. B 707:4904-4912(1997); Haubold, S., et al., “Strongly luminescent InP / ZnS core-shell nanoparticles,” Chemphyschem. 5:331-334(2001); Cros Gagneux, A., et al., “Surface chemistry of InP quantum dots: A comprehensive study,” J. Am. Chem. Soc. 132:18147-18157(2010); Micic, O. I., et al., “Synthesis and characterization of InP, GaP, and GalnP2 quantum dots,” J. Phys. Chem. 99:1154-7159(1995); Guzelian, A. A., et al., “Synthesis of size-selected, surface-passivated InP nanocrystals,” J. Phys. Chem.100:1212-1219 (1996); Lucey, DW, et al., "Monodispersed InP quantumdots prepared by colloidal chemistry in a non-coordinating solvent," Chem. Mater. 17:3154-3162 (2005); Lim, J., et al., "InP@ZnSeS, core@composition gradient shell quantum dots with enhanced stability," Chem. Mater. 23:4459-4463 (2011); and Zan, F., et al., "Experimental studies on blinking behavior of singleInP / ZnS quantum dots: Effects of synthetic conditions and UV irradiation," J. Phys. Chem. C 116:394-3950 (2012). However, such efforts have only achieved limited success in producing InP nanostructures with high quantum yields. .

[0141] In some embodiments, the InP core is doped. In some embodiments, the dopant of the nanocrystal core comprises a metal, including one or more transition metals. In some embodiments, the dopant is a transition metal selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, and combinations thereof. In some embodiments, the dopant comprises a non-metal. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP, or GaAs.

[0142] In some embodiments, the core is purified prior to depositing the shell. In some embodiments, the core is filtered to remove precipitate from the core solution.

[0143] In some embodiments, the diameter of the InP core is determined using quantum confinement. Quantum confinement in zero-dimensional nanocrystals such as quantum dots is caused by the spatial confinement of electrons within the crystal boundary. Once the diameter of the material is of the same order of magnitude as the de Broglie wavelength of the wave function, quantum confinement can be observed. The electrical and optical properties of nanoparticles deviate significantly from those of bulk materials. When the confinement size is large compared to the wavelength of the particle, the particle behaves as if it is free. During this state, the band gap remains at its original energy due to continuous energy states. However, as the confinement size decreases and reaches some limits, typically at the nanoscale, the energy spectrum becomes discrete. As a result, the band gap becomes size-dependent.

[0144] In some embodiments, the nanostructure is cadmium-free. As used herein, the term "cadmium-free" is intended to be a nanostructure containing less than 100ppm weight of cadmium. The Restriction of Hazardous Substances (RoHS) compliance definition requires that the cadmium must be no more than 0.01% by weight (100ppm) in the original homogeneous precursor material. The cadmium level in the Cd-free nanostructure of the present invention is limited by the trace metal concentration in the precursor material. The trace metal (including cadmium) concentration in the precursor material of the Cd-free nanostructure can be measured by inductively coupled plasma mass spectrometry (ICP-MS) analysis, and at the level of parts per billion (ppb). In some embodiments, the nanostructure "cadmium-free" contains less than about 50ppm, less than about 20ppm, less than about 10ppm, or less than about 1ppm of cadmium.

[0145] shell

[0146] In some embodiments, the nanostructure core comprises one or more shells. Exemplary materials for preparing the shells include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, Co, Au, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSc, PbTc, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, and combinations thereof.

[0147] In some embodiments, the shell is a mixture of at least two of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is a mixture of two of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is a mixture of three of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is a mixture of zinc and sulfur; zinc and selenium; zinc, sulfur and selenium; zinc and tellurium; zinc, tellurium and sulfur; zinc, tellurium and selenium; zinc, cadmium and sulfur; zinc, cadmium and selenium; cadmium and sulfur; cadmium and selenium; cadmium, selenium and sulfur; cadmium and zinc; cadmium, zinc and sulfur; cadmium, zinc and selenium; or cadmium, zinc, sulfur and selenium. In some embodiments, the shell is a mixture of zinc and selenium. In some embodiments, the shell is a mixture of zinc and sulfur.

[0148] Exemplary core / shell light-emitting nanostructures include, but are not limited to, (denoted as core / shell) CdSe / ZnSe and InP / ZnSe.

[0149] In some embodiments, the shell comprises ZnSe. The thickness of the shell can be controlled by varying the amount of precursor provided. For a given shell thickness, at least one of the precursors is optionally provided in an amount such that when the growth reaction is substantially complete, a shell of a predetermined thickness is obtained. In some embodiments, the molar ratio of the zinc source to the selenium source is between about 0.01:1 and about 1:1.5, about 0.01:1 and about 1:1.25, about 0.01:1 and about 1:1, about 0.01:1 and about 1:0.75, about 0.01:1 and about 1:0.5, about 0.01:1 and about 1:0.25, about 0.01:1 and about 1:0.05, about 0.05:1 and about 1:1.5, about 0.05:1 and about 1:1.25, about 0.05:1 and about 1:1, about 0.05:1 and about 1:0.75, about 0.05:1 and about 1:0.5, about 0.05:1 and about 1:0. 25, about 0.25:1 and about 1:1.5, about 0.25:1 and about 1:1.25, about 0.25:1 and about 1:1, about 0.25:1 and about 1:0.75, about 0.25:1 and about 1:0.5, about 0.5:1 and about 1:1.5, about 0.5:1 and about 1:1.25, about 0.5:1 and about 1:1, about 0.5:1 and about 1:0.75, about 0.75:1 and about 1:1.5, about 0.75:1 and about 1:1.25, about 0.75:1 and about 1:1, about 1:1 and about 1:1.5, about 1:1 and about 1:1.25, or about 1:1.25 and about 1:1.5.

[0150] The thickness of the ZnSe shell layer can be controlled by varying the amount of zinc and selenium sources provided and / or by using longer reaction times and / or higher temperatures.At least one of the sources is optionally provided in an amount such that when the growth reaction is substantially complete, a layer of predetermined thickness is obtained.

[0151] The thickness of the ZnSe shell can be determined using technology known to those skilled in the art. In some embodiments, the thickness of the inner shell is determined by comparing the average diameter of the nanostructure before and after adding the inner shell. In some embodiments, the average diameter of the nanostructure before and after adding the inner shell is determined by TEM. In some embodiments, the ZnSe shell has a thickness between: about 0.01nm and about 0.35nm, about 0.01nm and about 0.3nm, about 0.01nm and about 0.25nm, about 0.01nm and about 0.2nm, about 0.01nm and about 0.1nm, about 0.01nm and about 0.05nm, about 0.05nm and about 0.35nm, about 0.05nm and about 0.3nm, about 0.05nm and about 0.25nm, about 0.05nm and about 0.2nm, about 0.05nm and about 0.1nm, about 0.1nm and about 0.35nm, about 0.1nm and about 0.3nm, about 0.1nm and about 0.25nm, about 0.1nm and about 0.2nm, about 0.2nm and about 0.35nm, about 0.2nm and about 0.3nm, about 0.2nm and about 0.25nm, about 0.25nm and about 0.35nm, about 0.25nm and about 0.3nm, or about 0.3nm and about 0.35nm.

[0152] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc caproate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate or a mixture thereof. In some embodiments, the zinc source is zinc oleate, zinc caproate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate or a mixture thereof. In some embodiments, the zinc source is zinc oleate.

[0153] In some embodiments, the selenium source is an alkyl-substituted selenourea. In some embodiments, the selenium source is phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri (n-butyl) phosphine selenide, tri (sec-butyl) phosphine selenide, tri (tert-butyl) phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octane selenol, 1-dodecane selenol, selenol, elemental selenium, hydrogen selenide, bis (trimethylsilyl) selenide (selenoether), selenourea, and mixtures thereof. In some embodiments, the selenium source is tri (n-butyl) phosphine selenide, tri (sec-butyl) phosphine selenide, or tri (tert-butyl) phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.

[0154] In some embodiments, the ZnSe shell is synthesized under the existence of at least one nanostructure part.Part can for example strengthen the miscibility of nanostructure in solvent or polymer (allowing nanostructure to be distributed in whole composition so that described nanostructure does not gather together), increase the quantum yield of nanostructure, and / or keep nanostructure luminous (for example, when described nanostructure is incorporated in matrix).In some embodiments, be identical for InP nucleosynthesis and for shell synthetic (one or more) part.In some embodiments, be different for nucleosynthesis and for shell synthetic (one or more) part.After subsequent synthesis, any part on the surface of nanostructure all can be exchanged into the different parts with other desired properties. Examples of ligands are disclosed in U.S. Patent Nos. 7,572,395, 8,143,703, 8,425,803, 8,563,133, 8,916,064, 9,005,480, 9,139,770, and 9,169,435, and in U.S. Patent Application Publication No. 2008 / 0118755.

[0155] Suitable ligands for the synthesis of shells are known to those skilled in the art. In some embodiments, the ligand is a fatty acid selected from lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from dodecylamine, oleylamine, hexadecylamine, dioctylamine and octadecylamine. In some embodiments, the ligand is oleic acid.

[0156] In some embodiments, the nanostructure composition comprises InP / ZnSe / ZnS core-shell nanostructures, wherein the thickness of at least one of the ZnSe and ZnS shells is between 0.7 nm and 3.5 nm, wherein the nanostructures exhibit a photoluminescence quantum yield of 60 - 99%, wherein the nanostructures exhibit a full width at half maximum of 35 nm to 45 nm; and wherein the nanostructures exhibit an OD of about 1.0 to about 3.0 450 / peak. Such nanostructures and methods of making are disclosed in U.S. Application Publication Nos. 2017 / 0306227 and 20180199007.

[0157] In some embodiments, the nanostructure comprises a core comprising indium phosphide and at least two shells, wherein at least one of the shells comprises zinc, wherein the nanostructure exhibits a photoluminescence quantum yield between about 94% and about 100%, and wherein the nanostructure has a full width at half maximum of less than 45 nm. In some embodiments, the nanostructure is an InP / ZnSe / ZnS nanostructure. Such nanostructures and methods of making are disclosed in U.S. Patent Application No. 2020 / 0325396.

[0158] In some embodiments, the nanostructure composition comprises core-shell nanostructures surface-treated with zinc acetate and zinc fluoride. In some embodiments, the present disclosure provides a nanostructure composition comprising InP / ZnSe core-shell nanostructures. In some embodiments, the ZnSe shell has a thickness between about 0.01 nm and about 5 nm. In some embodiments, the nanostructures are quantum dots. Such nanostructures and methods of making are disclosed in U.S. Patent Application Publication No. 20210013377.

[0159] In some embodiments, the nanostructure composition comprises ZnSe 1- x Te x alloy nanocrystals, where 0 > X > 1. In some embodiments, the nanostructure comprises a core surrounded by at least one shell, wherein the core comprises ZnSe 1-x Te x , where 0 < x < 1, wherein the at least one shell is selected from ZnS, ZnSe, ZnTe, and alloys thereof, and wherein the full width at half maximum (FWHM) of the nanostructure is from about 20 nm to about 30 nm. Such nanostructures and methods of making are disclosed in U.S. Patent Application Publication No. 20210047563.

[0160] In some embodiments, the nanostructure comprises a nanocrystalline core and at least one shell, wherein the at least one shell comprises at least one metal fluoride of formula (I): MF4 (I), where: M = Zr, Hf or Ti. In some embodiments, the nanostructure comprises: (a) a core comprising ZnSe, at least one shell comprising ZnS, and at least one shell comprising HfF4; or (b) a core comprising ZnSe 1-x Te x with a core, where 0 < x < 1, at least one shell comprising ZnSe, and at least one shell comprising ZnS, and at least one shell comprising HfF4. Such nanostructures and methods of making are disclosed in U.S. Patent Application Publication No. 2021 / 0277307.

[0161] In some embodiments, the nanostructure comprises a core surrounded by at least one shell, wherein the core comprises ZnSe 1-x Te x , where 0 < x < 1, wherein the at least one shell comprises ZnS or ZnSe, and wherein the full width at half maximum (FWHM) of the nanostructure is between about 10 nm and about 30 nm. In some embodiments, the nanostructure is a ZnSe 1- x Te x / ZnSe / ZnS core / shell nanostructure. Such nanostructures and methods of making are disclosed in U.S. Patent Application Publication No. 20190390109.

[0162] In some embodiments, the nanostructure comprises a nanocrystalline core; and at least one shell disposed on the core, wherein the at least one shell comprises ZnS and a fluoride. In some embodiments, the nanostructure comprises: a core comprising ZnSe, and at least one shell comprising ZnS and ZnF2; a core comprising ZnSe, at least one shell comprising ZnSe, and at least one shell comprising ZnS and ZnF2; a core comprising ZnSe 1-x Te x with a core, where 0 < x < 1, and at least one shell comprising ZnS and ZnF2; or a core comprising ZnSe 1-x Te x with a core, where 0 < x < 1, at least one shell comprising ZnSe, and at least one shell comprising ZnS and ZnF2. Such nanostructures and methods of making are disclosed in U.S. Patent Application Publication No. 2021 / 0009900.

[0163] In some embodiments, the nanostructure comprises at least one fluorine-containing ligand bound to the surface of the nanostructure; wherein the fluorine-containing ligand is selected from fluorozincate, tetrafluoroborate and hexafluorophosphate; or a fluoride anion bound to the surface of the nanostructure; and wherein the nanostructure composition exhibits a photoluminescence quantum yield between about 70% and about 90%. Such nanostructures and methods of making are disclosed in U.S. Patent Application Publication No. 2020 / 0299575.

[0164] In some embodiments, the nanostructure comprises Ag, In, Ga and S (AIGS). In some embodiments, the nanostructure has a peak emission wavelength (PWL) in the range of 480-545nm, wherein at least about 80% of the emission is band edge emission, and wherein the nanostructure exhibits a quantum yield (QY) of 80-99.9%. Such nanostructures and methods of manufacture are disclosed in U.S. Patent No. 10,927,294.

[0165] Membranes, devices and applications

[0166] Microparticle group is optionally embedded in the matrix (for example, organic polymer, the polymer containing silicon, inorganic, glass and / or other matrix) of forming film.This film can be used in the production of nanostructure phosphor, and / or is incorporated into device such as LED, backlight, downlight or other display or lighting unit or optical filter.Exemplary phosphor and lighting unit can for example generate the light of specific color by being incorporated in or approaching the nanostructure group with emission maximum under the wavelength of expectation, or generate wide color range by being incorporated into two or more different nanostructure groups with different emission maximum.Various suitable matrixes are known in the art.See for example U.S. Patent number 7,068,898 and U.S. Patent Application Publication Nos. 2010 / 0276638, 2007 / 0034833 and 2012 / 0113672. Exemplary nanostructure phosphor films, LEDs, backlight units, etc. are described in, for example, U.S. Patent Application Publication Nos. 2010 / 0276638, 2012 / 0113672, 2008 / 0237540, 2010 / 0110728, and 2010 / 0155749, and U.S. Patent Nos. 7,374,807, 7,645,397, 6,501,091, and 6,803,719.

[0167] In some embodiments, the nanostructure film is used to form a display device. As used herein, a display device refers to any system having an illuminated display. Such devices include, but are not limited to, devices covering liquid crystal displays (LCDs), televisions, computers, mobile phones, smart phones, personal digital assistants (PDAs), gaming devices, electronic reading devices, digital cameras, and the like.

[0168] In some embodiments, the present disclosure provides a nanostructure molded article comprising:

[0169] (a) a first conductive layer;

[0170] (b) a second conductive layer; and

[0171] (c) a nanostructure layer between the first conductive layer and the second conductive layer, wherein the nanostructure layer comprises a population of silica particles comprising nanostructures embedded in a matrix.

[0172] In some embodiments, the present disclosure provides a nanostructure film comprising:

[0173] (a) at least one population of silica particles comprising a population of silica particles including nanostructures; and

[0174] (b) at least one organic resin.

[0175] As used herein, the term "embedded" is used to indicate that the microparticles are wrapped or encapsulated within a matrix material. In some embodiments, the microparticles are uniformly distributed throughout the matrix material. In some embodiments, the microparticles are distributed according to an application-specific uniformity distribution function.

[0176] The host material can be any suitable host matrix material that can hold particulate. Suitable host material can be chemically and optically compatible with particulate and any surrounding packaging material or layer for applying the nanostructure film to the device. Suitable host material can include non-yellowing optical materials that are transparent to both primary light and secondary light, thereby allowing both primary light and secondary light to be transmitted through the host material. Host material can include polymer and organic and inorganic oxides. Suitable polymers used in the host material can be any polymer known to those of ordinary skill that can be used for such purposes. The polymer can be substantially translucent or substantially transparent. Matrix materials may include, but are not limited to, epoxies, acrylates, norbornenes, polyethylene, poly(vinyl butyral):poly(vinyl acetate), polyureas, polyurethanes; silicones and silicone derivatives, including, but not limited to, aminosilicones (AMS), polyphenylmethylsiloxanes, polyphenylalkylsiloxanes, polydiphenylsiloxanes, polydialkylsiloxanes, silsesquioxanes, fluorinated silicones, and vinyl and hydride substituted silicones; acrylic polymers and copolymers formed from monomers, including, but not limited to, methyl methacrylate, butyl methacrylate, and lauryl methacrylate; styrene-based polymers such as polystyrene, aminopolystyrene (APS), and poly(acrylonitrile vinyl styrene) (AES); polymers crosslinked with difunctional monomers, such as divinylbenzene; crosslinking agents suitable for crosslinking ligand materials, epoxides combined with ligand amines (e.g., APS or polyethyleneimine ligand amines) to form epoxy resins, and the like.

[0177] In some embodiments, the matrix material further includes scattering beads such as TiO2 beads, ZnS beads, or glass beads that can improve the light conversion efficiency of the nanostructure film. In some embodiments, the matrix material can include a light blocking element.

[0178] In some embodiments, the matrix material can have low oxygen and moisture permeability, exhibit high light and chemical stability, exhibit a favorable refractive index, and adhere to the outer surface of the nanostructure, thereby providing an airtight seal to protect the nanostructure. In another embodiment, the matrix material can be cured with UV or thermal curing methods to facilitate roll-to-roll processing.

[0179] In some embodiments, the nanostructure film further comprises one or more barrier layers adjacent to the nanostructure film, and the nanostructure film has low oxygen and water permeability and protects the nanostructure from degradation. In other embodiments, the nanostructure film has at least one surface exposed to environmental conditions. In some embodiments, the nanostructure film does not comprise a barrier layer. This is possible because the microparticles containing silicon dioxide have low oxygen and water permeability. The use of the microparticles containing silicon dioxide eliminates the use of barrier layers, thereby reducing the cost and complexity of the device comprising the nanostructure film.

[0180] In some embodiments, the nanostructure film can be formed by mixing the particles in a polymer (e.g., a photoresist) and casting the particle-polymer mixture on a substrate, mixing the particles with monomers and polymerizing them together, mixing the particles in a sol-gel to form an oxide, or any other method known to those skilled in the art.

[0181] In some embodiments, the formation of the nanostructure film may include a film extrusion process. The film extrusion process may include: forming a homogenous mixture of matrix material and microparticles, introducing the homogenous mixture into a top mounted hopper, which feeds the extruder. In some embodiments, the homogenous mixture may be in the form of pellets. The film extrusion process may further include extruding the nanostructure film from a slit die and passing the extruded nanostructure film through a cooling roller. In some embodiments, the extruded nanostructure film may have a thickness of less than about 75 μm, for example, in the range of about 70 μm to about 40 μm, about 65 μm to about 40 μm, about 60 μm to about 40 μm, or about 50 μm to about 40 μm. In some embodiments, the nanostructure film has a thickness of less than about 10 μm. In some embodiments, the formation of the nanostructure film may optionally include a secondary process, followed by a film extrusion process. The secondary process may include processes such as coextrusion, thermoforming, vacuum forming, plasma treatment, molding and / or embossing to provide texture to the top surface of the nanostructure film layer. A textured top surface nanostructure film can help improve, for example, defined optical diffusion properties and / or defined angular optical emission properties of the nanostructure film.

[0182] In some embodiments, the nanostructure composition is used to form a nanostructure molded article. In some embodiments, the nanostructure molded article is a liquid crystal display (LCD) or a light emitting diode (LED). In some embodiments, the nanostructure composition is used to form an emission layer of a lighting device. The lighting device can be used in various applications, such as flexible electronics, touch screens, monitors, televisions, mobile phones, and any other high-definition displays. In some embodiments, the lighting device is a light emitting diode or a liquid crystal display. In some embodiments, the lighting device is a quantum dot light emitting diode (QLED). Examples of QLED are disclosed in U.S. Patent Application No. 15 / 824,701, which is incorporated herein by reference in its entirety. In some embodiments, the core-shell nanostructure is InP / ZnSe. In some embodiments, the molded article does not include a separate barrier layer for protecting the nanostructure from oxygen and / or moisture.

[0183] In some embodiments, the present disclosure provides a light emitting diode comprising:

[0184] (a) a first conductive layer;

[0185] (b) a second conductive layer; and

[0186] (c) an emissive layer between the first conductive layer and the second conductive layer, wherein the emissive layer comprises (i) silica particles including at least one nanostructure population.

[0187] In some embodiments, the core-shell nanostructure is CdSe / ZnSe or InP / ZnSe.

[0188] In some embodiments, the emissive layer is a nanostructure film.

[0189] In some embodiments, the light emitting diode comprises a first conductive layer, a second conductive layer and an emission layer, wherein the emission layer is arranged between the first conductive layer and the second conductive layer. In some embodiments, the emission layer is a thin film comprising silica particles, and the silica particles comprise one or more nanostructure groups.

[0190] In some embodiments, the light emitting diode comprises additional layers such as a hole injection layer, a hole transport layer, and an electron transport layer between the first conductive layer and the second conductive layer. In some embodiments, the hole injection layer, the hole transport layer, and the electron transport layer are thin films. In some embodiments, the layers are stacked on a substrate.

[0191] When voltage is applied to the first conductive layer and the second conductive layer, holes injected at the first conductive layer move to the emission layer via the hole injection layer and / or the hole transport layer, and electrons injected from the second conductive layer move to the emission layer via the electron transport layer. Holes and electrons recombine in the emission layer to generate excitons. In some embodiments, the hole transport layer comprises poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)](TFB).

[0192] In some embodiments, the nanostructure film is incorporated into a glass LCD display device. The LCD display device may include a nanostructure film formed directly on a light guide plate (LGP) without an intermediate substrate or barrier layer. In some embodiments, the nanostructure film may be a thin film. In some embodiments, the nanostructure film may have a thickness of 500 μm or less, 100 μm or less, or 50 μm or less. In some embodiments, the nanostructure film is a thin film with a thickness of about 15 μm or less. In some embodiments, the core-shell nanostructure is CdSe / ZnSe or InP / ZnSe.

[0193] The LGP may include an optical cavity having one or more sides, including at least a top side, comprising glass. Glass provides excellent resistance to impurities including moisture and air. In addition, glass can be formed into a thin substrate while maintaining structural rigidity. Thus, the LGP may be formed at least in part from a glass surface to provide a substrate with sufficient barrier and structural properties.

[0194] In some embodiments, nanostructure film can be formed on LGP. In some embodiments, the nanostructure film comprises a group of silica particles, and the silica particles comprise one or more nanostructure groups embedded in a matrix material such as a resin. The nanostructure film can be formed on LGP by any method known in the art such as wet coating, paint coating, spin coating or screen printing. In some embodiments, the nanostructure film is formed by extrusion. After deposition, the resin of the nanostructure film can be cured. In some embodiments, the resin of one or more nanostructure films can be partially cured, further processed, and then finally cured. The nanostructure film can be deposited as a layer or deposited as a separate layer, and the separate layer can include different properties. The width and height of the nanostructure film can be any desired size, depending on the size of the viewing panel of the display device. For example, the nanostructure film can have a relatively small surface area in a small display device embodiment (such as a watch and a mobile phone), or the nanostructure film can have a large surface area for a large display device embodiment (such as a TV and a computer monitor).

[0195] In some embodiments, the present disclosure provides a display backlight unit (BLU) comprising:

[0196] (a) at least one primary light source emitting primary light;

[0197] (b) a light guide plate (LGP) optically coupled to the at least one primary light source, whereby the primary light is uniformly transmitted through the LGP; and

[0198] (c) an extruded film disposed on the LGP, wherein the primary light is uniformly transmitted through the LGP and into the extruded film;

[0199] wherein the extruded film is not directly physically coupled to the LGP and comprises one or more populations of nanostructures configured to emit secondary light, wherein at least a portion of the primary light is absorbed by the nanostructures and re-emitted by the nanostructures as the secondary light, and wherein the BLU does not comprise a barrier layer.

[0200] In some embodiments, the one or more populations of nanostructures are encapsulated by an inorganic material. In some embodiments, the inorganic material comprises silica particles.

[0201] In some embodiments, the optically transparent substrate is formed on the nanostructure film by any method known in the art such as vacuum deposition, vapor deposition, etc. The optically transparent substrate can be optionally configured to provide an environmental seal to the layer and / or structure below the nanostructure film. In some embodiments, a light blocking element may be included in the optically transparent substrate. In some embodiments, the light blocking element may be included in a second polarizing filter, which may be located between substrate and the nanostructure film. In some embodiments, the light blocking element may be a dichroic filter, for example, which can reflect primary light (for example, a combination of blue light, UV light, or UV light and blue light) while transmitting secondary light. The light blocking element may include a specific UV light filtering component to remove any unconverted UV light from red and green sub-pixels, and / or UV light from blue sub-pixels.

[0202] In some embodiments, the nanostructure film is incorporated into a display device by "on-chip" placement. As used herein, "on-chip" refers to placing the nanostructure into an LED cup. In some embodiments, the nanostructure is dissolved in a resin or fluid to fill the LED cup. In some embodiments, the LED cup does not further include a barrier layer for protecting the nanostructure from oxygen and / or moisture.

[0203] In some embodiments, the nanostructures are incorporated into a display device by "near-chip" placement. As used herein, "near-chip" refers to coating the top surface of an LED component with nanostructures so that the exiting light passes through the nanostructure film.

[0204] In some embodiments, the present invention provides a display device comprising:

[0205] (a) a display panel to emit a first light;

[0206] (b) a backlight unit configured to provide the first light to the display panel; and

[0207] (c) A color filter comprising at least one pixel region, wherein the pixel region comprises a color conversion layer.

[0208] In some embodiments, the color filter comprises at least 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 pixel areas. In some embodiments, when blue light is incident on the color filter, red light, white light, green light and / or blue light can be emitted through the pixel areas, respectively. In some embodiments, the color filter is described in U.S. Patent Application Publication No. 2017 / 153366.

[0209] In some embodiments, each pixel region includes a color conversion layer. In some embodiments, the color conversion layer includes a nanostructure described herein configured to convert incident light into light of a first color. In some embodiments, the color conversion layer includes a nanostructure described herein configured to convert incident light into blue light.

[0210] In some embodiments, the display device comprises 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 color conversion layers. In some embodiments, the display device comprises one color conversion layer, and the color conversion layer comprises a nanostructure described herein. In some embodiments, the display device comprises two color conversion layers, and the color conversion layers comprise a nanostructure described herein. In some embodiments, the display device comprises three color conversion layers, and the color conversion layers comprise a nanostructure described herein. In some embodiments, the display device comprises four color conversion layers, and the color conversion layers comprise a nanostructure described herein. In some embodiments, the display device comprises at least one red conversion layer, at least one green conversion layer, and at least one blue conversion layer.

[0211] In some embodiments, the color conversion layer has a thickness between about 3 μm and about 10 μm, about 3 μm and about 8 μm, about 3 μm and about 6 μm, about 6 μm and about 10 μm, about 6 μm and about 8 μm, or about 8 μm and about 10 μm. In some embodiments, the color conversion layer has a thickness between about 3 μm and about 10 μm.

[0212] The nanostructure color conversion layer can be deposited by any suitable method known in the art, including but not limited to paint, spray, solvent spray, wet coating, adhesive coating, spin coating, tape coating, roller coating, flow coating, inkjet printing (inkjet printing), photoresist patterning, drop casting, scraping, spray deposition or its combination. In some embodiments, the nanostructure color conversion layer is deposited by photoresist patterning. In some embodiments, the nanostructure color conversion layer is deposited by inkjet printing.

[0213] Inkjet Printing

[0214] The formation of the film using the dispersion of nanostructure in organic solvent is often realized by coating technology such as spin coating. However, these coating technologies are generally not suitable for the formation of thin films on large areas, and do not provide the means for patterning the deposited layer, and therefore have limited uses. Inkjet printing allows to place with the patterning of large-scale accurate thin films at low cost. Inkjet printing also allows the accurate patterning of nanostructure layers, allows the pixels of printing displays, and eliminates photolithography patterning. Therefore, inkjet printing is very attractive for industrial applications, particularly in display applications.

[0215] The solvent used for inkjet printing routinely is dipropylene glycol monomethyl ether acetate (DPMA), poly glycidyl methacrylate (PGMA), diethylene glycol monoethyl ether acetate (EDGAC) and propylene glycol methyl ether acetate (PGMEA). Volatile solvents are also frequently used in inkjet printing because they allow rapid drying. Volatile solvents include ethanol, methanol, 1-propyl alcohol, 2-propyl alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate and tetrahydrofuran (THF). Conventional nanostructures are generally insoluble in these solvents. However, the hydrophilicity of the increase of the nanostructure comprising a poly (alkylene oxide) part allows the solubility in these solvents to increase.

[0216] In some embodiments, the microparticles for inkjet printing described herein are dispersed in a solvent selected from the group consisting of DPMA, PGMA, EDGAC, PGMEA, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, chloroform, chlorobenzene, cyclohexane, hexane, heptane, octane, hexadecane, undecane, decane, dodecane, xylene, toluene, benzene, octadecane, tetradecane, butyl ether, or a combination thereof. In some embodiments, the nanostructure comprising the poly(alkylene oxide) ligand for inkjet printing described herein is dispersed in a solvent selected from the group consisting of DPMA, PGMA, EDGAC, PGMEA, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, or a combination thereof.

[0217] For application by inkjet printing or microdispensing, the inkjet composition comprising the microparticles should be dispersed in a suitable solvent. The solvent must be capable of dispersing the microparticle composition and must not have any deleterious effect on the selected print head.

[0218] In some embodiments, the inkjet composition further comprises one or more additional components such as surface active compounds, lubricants, wetting agents, dispersants, hydrophobic agents, binders, flow improvers, defoamers, deaerators, diluents, adjuvants, colorants, dyes, pigments, sensitizers, stabilizers and inhibitors.

[0219] In some embodiments, the microparticle compositions described herein comprise between about 0.01 wt % and about 20 wt % of the inkjet composition. In some embodiments, the nanostructures comprising the poly(alkylene oxide) ligands comprise between about 0.01 wt % and about 20 wt %, about 0.01 wt % and about 15 wt %, about 0.01 wt % and about 10 wt %, about 0.01 wt % and about 5 wt %, about 0.01 wt % and about 2 wt %, about 0.01 wt % and about 1 wt %, about 0.01 wt % and about 0.01 wt %, about 0.01 wt % and about 0.01 wt %, about 0.01 wt % and about 0.01 wt %, about 0.01 wt % and about 0.01 wt %. %, about 0.05 wt % and about 20 wt %, about 0.05 wt % and about 15 wt %, about 0.05 wt % and about 10 wt %, about 0.05 wt % and about 5 wt %, about 0.05 wt % and about 2 wt %, about 0.05 wt % and about 1 wt %, about 0.05 wt % and about 0.1 wt %, about 0.1 wt % and about 20 wt %, about 0.1 wt % and about 15 wt %, about 0.1 wt % and about 10 wt %, about 0.1 wt % and about 5 wt %, about 0.1 wt % and about 2 wt %, about 0.1 wt % and about 1 wt %, about 0.5 wt % and about 20 wt %, about 0.5 wt % and about 15 wt %, about 0.5 wt % and about 10 wt %, about 0.5 wt % and about 5 wt %, about 0.5 wt % and about 2 wt %, about 0.5 wt % and about 1 wt %, about 1 wt % and about 20 wt %, about 1 wt % and about 15 wt %, about 1 wt % and about 10 weight %, about 1 weight % and about 5 weight %, about 1 weight % and about 2 weight %, about 2 weight % and about 20 weight %, about 2 weight % and about 15 weight %, about 2 weight % and about 10 weight %, about 2 weight % and about 5 weight %, about 5 weight % and about 20 weight %, about 5 weight % and about 15 weight %, about 5 weight % and about 10 weight %, about 10 weight % and about 20 weight %, about 10 weight % and about 15 weight %, or about 15 weight % and 20 weight %.

[0220] In some embodiments, the inkjet composition comprising the microparticles or microparticle compositions described herein is used in the formulation of an electronic device. In some embodiments, the inkjet composition comprising the microparticles or microparticle compositions described herein is used in the formulation of an electronic device selected from the group consisting of nanostructure films, display devices, lighting devices, backlight units, color filters, surface luminescent devices, electrodes, magnetic storage devices, and batteries. In some embodiments, the inkjet composition comprising the microparticles or microparticle compositions described herein is used in the formulation of a light-emitting device.

[0221] Example

[0222] The following examples of the products and methods described herein are illustrative and non-limiting. Suitable modifications and adjustments to the various conditions, formulations and other parameters commonly encountered in the art, as well as modifications and adjustments that are clear to those skilled in the art in view of this disclosure, are within the spirit and scope of the present invention.

[0223] Example 1

[0224] Nanostructure ligand exchange process

[0225] The development of silica microparticles involves transferring the nanostructures from nonpolar solvents to water via ligand exchange. The typical process involves the following steps.

[0226] • Prepare the potassium or tetramethylammonium salt of MPA by mixing potassium hydroxide or tetramethylammonium hydroxide to mercaptopropionic acid (MPA).

[0227] • DI water, MPA salt and butanol were mixed with the QD solution in toluene / heptane in a flask.

[0228] Heat the flask to 60°C for 3 hours

[0229] Maintain solution to allow phase separation of aqueous and organic layers

[0230] Separation and purification of the aqueous phase

[0231] The water-soluble nanostructures were then used for the synthesis of QD-silica particles. Various processes were developed for the synthesis of QD-silica particles.

[0232] Example 2

[0233] Process 1: Calcium silicate encapsulated QD particles:

[0234] Typical processes are summarized in Figure 2 The details of the process are as follows

[0235] • 2 mL of aqueous dispersion of QDs (9-10 wt% inorganic content) + 3.4 mL of water + 0.15 ml of (3-mercaptopropyl)trimethoxysilane (MPTMS) were stirred at 80°C for 5 minutes.

[0236] • Add 2.8 mL of 25 wt% lithium silicate (LiSiL) solution with good stirring.

[0237] • Add 16.5 ml of 1.3 wt% span 80 / octadecene (ODE) solution with good stirring. The solution becomes milky, indicating the formation of a microemulsion.

[0238] • The emulsion was passed through a 6 μm filter 3-4 times for homogenization.

[0239] • Remove water from the microemulsion by heating in vacuum at 80° C. This takes about 10-15 minutes at 10 torr vacuum.

[0240] • Microparticles were separated by centrifugation (3000-4000 rpm for 5 minutes).

[0241] • The particles were purified by washing twice with acetone and twice with ethanol.

[0242] • The QD-silicate particles were dispersed in 7 ml of 1 M calcium chloride solution and stirred at 60 °C for 30 minutes.

[0243] The product was purified by centrifugation and washing with ethanol (2 times).

[0244] The obtained product is dried to make a powder and dispersed in a carrier solvent.

[0245] • The process produces ~95% calcium silicate particles per batch with ~20 wt% QD loading.

[0246] The process produces a fine powder of calcium silicate particles containing nanostructures. In one embodiment, the silicate particles containing nanostructures are composed of red and green quantum dots when exposed to white light and blue light. As expected, when exposed to blue light, green and red fluorescence emissions are observed, which indicates the presence of quantum dots in the silicate particles.

[0247] The microparticles were further characterized by scanning electron microscopy (SEM). Figures 3A-3C is a SEM image of a drop coated film containing calcium silicate particles of nanostructures on a substrate. The particles were found to be well defined and uniform with a rough surface topology. The particle size was measured from this image. The average particle size was found to be 2.9 ± 0.9 μm ( Figure 4 ).

[0248] Test specimens of quantum dot enhanced film (QDEF) were made using poly(methyl methacrylate) (PMMA) and calcium silicate microparticles containing quantum dots to study the stability / reliability of the particles under operating conditions. In a typical process, 1.5 gm of QD-silicate particles were mixed with a minimum amount of IBOA to make a paste. ~15 gm of PMMA pellets were added to the paste and mixed thoroughly to make a homogenous mixture, and sheets were made using an extruder. The stability of the QD-silicate microparticles was evaluated by monitoring the emitted power from the sheet as a function of time under the following conditions.

[0249] 1) At 50°C at high throughput (1, 10 and 68X)

[0250] 2) At 80°C under accelerated conditions at high throughput (1 and 10X)

[0251] 3) Store at 85°C in dark

[0252] 4)Store at 60℃ and 90% relative humidity

[0253] Figures 5A-5D The emitted power from the sheet is shown over a 1000 hour period. It was found that the sheet Figure 5A ) and 80℃( Figure 5B ) maintained about 90% emission power at 1X & 10X flux, indicating satisfactory stability / reliability of the membrane. However, it was found that the stability of the membrane was degraded under very harsh conditions (68x flux at 50°C; Figure 5A ) is insufficient. In addition, for storage at 85°C in the dark ( Figure 5C ) and stored at 60°C / 90% relative humidity ( Figure 5D ), no significant changes in the emitted power of the sheet were observed. This indicates that the QDEF has good stability under most of the tested conditions.

[0254] Example 3

[0255] Process 2: Calcium silicate encapsulated QD particles:

[0256] In another approach, QD-silicate microparticles were synthesized by directly cross-linking silicate ions using Ca++ ions in a microemulsion. The process flow is shown in Figure 6 middle.

[0257] The details of the process are as follows

[0258] • 16.5 ml of 3 wt% span 80 / ODE solution was stirred at 600 rpm. 2.8 mL of 25 wt% lithium silicate solution was added with good stirring. The resulting mixture became milky, indicating the formation of a microemulsion.

[0259] • The solution was passed through a 6 μm filter for homogenization. This solution was called "Microemulsion 1".

[0260] · 2 mL of aqueous dispersion of QDs (9-10 wt% inorganic content) + 3.4 mL of water + 0.15 ml of MPTMS were stirred at 60°C for 5 minutes.

[0261] 27.5 ml of 3 wt% span 80 / ODE solution was stirred at 600 rpm. The above QD solution was added dropwise. The resulting mixture became milky, indicating the formation of a microemulsion.

[0262] • This solution was also passed through a 6 um filter for homogenization. This solution was called "Microemulsion 2".

[0263] Microemulsions 1 and 2 were mixed and kept under stirring for 30 minutes.

[0264] 15 ml of 3 wt% span 80 / ODE solution was stirred at 600 rpm. 3 ml of 2M calcium chloride solution was added dropwise. The resulting mixture became milky, indicating the formation of a microemulsion.

[0265] • The solution was passed through a 6 micron filter for homogenization. This solution was called Microemulsion 3.

[0266] Finally, microemulsion 3 was added to the mixture of microemulsions 1 & 2 and the resulting mixture was kept under stirring for 30 minutes for silicate precipitation

[0267] • Finally, the particles were separated by centrifugation and purified by washing with acetone and ethanol.

[0268] • The powder is dried and stored in a carrier solvent.

[0269] Characterization of microparticles by scanning electron microscopy ( Fig. 7A and 7B The QD-calcium silicate particles were spherical with a smooth surface texture. The size of the particles was found to be in the submicron to 8 micron range ( Figure 7C ).

[0270] Example 4

[0271] Process 3: Silica-encapsulated QD microparticles:

[0272] Typical processes are summarized in Figure 8 The details of the process are as follows

[0273] • Add 3 ml of water to 2 ml of QD solution and heat the resulting solution to 60 °C.

[0274] · Add 0.15 ml of MPTMS to the above solution and keep the solution at 60°C for 5 minutes under stirring conditions (500 rpm)

[0275] • To this solution was mixed 3 ml of LiSil solution under stirring for 10 minutes.

[0276] - In the next step, a microemulsion was made by adding 24 ml of Span 80 / ODE (3 wt%) to the QD / LiSil solution and the microemulsion was homogenized by passing through a 5 μm syringe filter.

[0277] • Remove water from the homogenized microemulsion by heating it in open air at 100°C for 60 minutes under stirring conditions (500-750 rpm range)

[0278] Prepare an acetic acid microemulsion by mixing 3 ml of glacial acetic acid in 15 ml of ODE / Span 80 (3 wt%) and homogenizing by passing through a 5 um filter. Add this microemulsion to the above microemulsion.

[0279] The resulting microemulsion was maintained at 100°C for an additional 45 minutes to complete the condensation reaction.

[0280] • Finally, the microparticles were separated by centrifugation and purified by washing with acetone and ethanol.

[0281] • The silica powder is dried and stored in a carrier solvent.

[0282] SEM was used to characterize the QD-silica particles ( Figures 9A-9D ). It was found that QD-silica particles have a very rough surface texture ( Figures 9A-9C ), wherein the size is in the range of 0.5 to 12 micrometers ( Fig.9D ).

[0283] Based on the input materials, this process is expected to produce a quantum dot loading of ~20 wt% in the QD-silica particles. The surface area and pore size of the silica particles were analyzed by BET isotherms (Table 1). The surface area was found to be ~39.36 m 2 / gm, with a pore size of 30nm and 0.34cm 3 / g pore volume (Table 1).

[0284] Table 1

[0285]

[0286] The quantum dot loading can be reduced by increasing the amount of LiSil solution ( Figures 10A-10D ). In the next step, the QD loading in the silica particles is reduced by adding lithium silicate. In this process, the QD loading in the silica particles is expected to be ~10 wt%.

[0287] The QD-silica particles were found to be well defined with visible pores on the surface (Figure 11). In this case, the size of the particles was found to be in the range of 6-22 μm.

[0288] Test specimens of quantum dot enhanced film (QDEF) were made using PMMA and QD-silica particles to study the stability or reliability of the particles under operating conditions. In a typical process, 1.5 gm of QD-silica particles were mixed with a minimum amount of IBOA to make a paste. ~15 gm of PMMA pellets were added to the paste and mixed thoroughly to make a homogeneous mixture, and sheets were made using an extruder. The sheets were analyzed using SEM to visualize the distribution of particles in the PMMA matrix and any morphological changes due to extrusion. Figures 11A-11C is a SEM image of a cross section of the extruded sheet, showing uniform distribution of particles in the film. The QD-silica particles were found to be intact after extrusion, indicating their robustness and stability.

[0289] The stability of the QD-silica particles was evaluated by monitoring the emission power from the sheet as a function of time under the following conditions.

[0290] • At 50°C at high throughput (1, 10 and 68X).

[0291] • At 80°C under accelerated conditions at high throughput (1 and 10X).

[0292] Store at 85°C away from light.

[0293] Store at 60°C and 90% relative humidity

[0294] Figures 12A-12D The emitted power from the sheet is shown over a 500 hour period. The sheet was found to be Fig. 12B ) and at 80°C at 1X flux ( Fig.12D ) maintained more than 90% of the transmitted power, indicating satisfactory stability / reliability as per product requirements. However, the stability of the membrane was found to be impaired under very harsh conditions (68x flux ( Fig. 12B )&10X at 80C( Fig.12D )) is insufficient. In addition, for storage at 85°C in the dark ( Fig. 12A ) and stored at 60°C / 90% relative humidity ( Fig. 12C ), no significant changes in the emission power of the sheet were observed. This indicates that the QDEF film exhibits good stability.

[0295] Example 5

[0296] Process 4: Calcium silicate encapsulated QD particles:

[0297] Typical processes are summarized in Fig.13 The details of the process are as follows:

[0298] • Add 3 ml of water to 2 ml of QD solution and heat the resulting solution to 60 °C.

[0299] · To the above solution, 0.15 ml of MPTMS was added, and the solution was maintained at 60° C. for 5 minutes under stirring conditions (500 rpm).

[0300] • To this solution was mixed 3 ml of LiSil solution under stirring for 10 minutes.

[0301] - In the next step, a microemulsion was made by adding 24 ml of Span 80 / ODE (3 wt%) to the QD / LiSil solution and the microemulsion was homogenized by passing through a 5 μm syringe filter.

[0302] • Water was removed from the homogenized microemulsion by heating it in open air at 100°C for 60 minutes under stirring conditions (500-750 rpm range).

[0303] • Dissolve 1.4 gm of calcium chloride in 6 ml of water. Prepare a microemulsion by mixing the calcium chloride solution in 24 ml of ODE / Span 80 (3 wt%) and homogenize by passing through a 5 μm filter. Add this microemulsion to the above microemulsion.

[0304] The resulting microemulsion was kept at 100°C for another 45 minutes to complete the crosslinking reaction.

[0305] • Finally, the particles were separated by centrifugation and purified by washing with acetone and ethanol.

[0306] Dry the powder and store it in a carrier solvent

[0307] Scanning electron microscopy was used to characterize the QD-calcium silicate particles, e.g. Figures 14A-14D It was found that the QD-calcium silicate particles have a very rough surface texture ( Figures 14A-14C ), where the size is in the range of 4 to 15 microns ( Fig.14D ).

[0308] Figures 15A-15D The emitted power from the sheet over a 1600 hour period is shown. The sheet was found to be Fig.15A ) and at 80°C at 1X flux ( Fig. 15B ) maintained more than 90% of the transmitted power, indicating satisfactory stability / reliability. However, the stability of the membrane was found to be reduced under very harsh conditions (68x flux ( Fig.15A )&10X( Fig. 15B )) is insufficient. In addition, for storage at 85°C in the dark ( Fig. 15C) and stored at 60°C / 90% relative humidity ( Fig.15D ), no significant changes in the emission power of the sheet were observed. This indicates that the QDEF has good stability.

[0309] Example 6

[0310] This example provides microparticles containing silicate derived from ammonium silicate instead of the lithium silicate in Example 4. Fig.16A and 16B As shown in , various sizes of microparticles ranging from submicron to about 10 μm are obtained. Fig. 16C As shown in FIG. , the composition of the nanoparticles consists of CdSe / ZnSe nanostructures and silica.

[0311] Example 7

[0312] This example provides silicate-containing microparticles derived from ammonium silicate using an emulsion process. Fig.17A and 17B As shown in , various sizes of microparticles ranging from submicron to about 10 μm are obtained. Fig. 17C As shown in FIG, the composition of the nanoparticles consists of CdSe / ZnSe nanostructures and calcium silicate.

[0313] Example 8

[0314] This example provides silicate-containing microparticles derived from lithium silicate using an emulsion process. Fig.18A and 18B As shown in , various sizes of microparticles ranging from submicron to about 6 μm are obtained. Fig. 18C As shown in FIG, the composition of the nanoparticles consists of CdSe / ZnSe nanostructures and calcium silicate.

[0315] Although various embodiments have been described above, it should be understood that they are presented only as examples and not limitations. It will be apparent to those skilled in the relevant art that various changes in form and detail may be made therein without departing from the spirit and scope of the invention. Therefore, the breadth and scope should not be limited by any of the above exemplary embodiments, but should only be limited according to the appended claims and their equivalents.

[0316] All publications, patents, and patent applications mentioned in this specification are indicative of the levels of skill of those skilled in the art to which the invention pertains, and are incorporated herein by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference.

Claims

1. A composition comprising a population of nanostructures comprising nanocrystalline cores, wherein the nanostructures are embedded in silica particles.

2. The composition of claim 1, wherein the nanocrystalline core is selected from the group consisting of Si, Ge, Sn, Se, Te, B, C, P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, Ag1nGaS, and combinations thereof.

3. The composition of claim 1 or 2, wherein the nanocrystal core comprises InP.

4. The composition of claim 1 or 2, wherein the nanocrystal core comprises CdSe.

5. The composition of any one of claims 1-4, wherein the nanocrystalline core comprises at least one shell. The composition of claim 5 , wherein the at least one shell is ZnSe.

7. The composition of claim 5, wherein the at least one shell is ZnS.

8. The composition of claim 1, wherein the nanostructures comprise silver, indium, gallium, and sulfur (AIGS).

9. The composition of any one of claims 1 to 8, wherein the silicate particles have a diameter of about 1 μm to about 20 μm.

10. The composition of any one of claims 1-9, wherein the silica microparticles have an average particle size of about 2 μm to about 12 μm.

11. A method for preparing a composition according to any one of claims 1 to 10, comprising: (a) mixing the nanostructure and metal or ammonium silicate in water; (b) adding the blend obtained in (a) to a solution comprising a nonionic surfactant in a nonpolar aprotic solvent and mixing to obtain a first microemulsion; (c) removing water from the first microemulsion obtained in (b); (d) mixing acetic acid, a nonionic surfactant, and a nonpolar aprotic solvent to obtain a second microemulsion; (e) blending the first and second microemulsions to obtain silica particles containing the nanostructures; and (f) isolating the microparticles obtained in (e).

12. The method of claim 11, wherein prior to blending in (e), the first and second microemulsions are passed through a filter having pores smaller than 10 μm.

13. The method of claim 11 or 12, wherein the non-polar aprotic solvent comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, or squalane, or a combination thereof.

14. The method of claim 13, wherein the non-polar aprotic solvent comprises 1-octadecene.

15. A nanostructured film comprising: (a) a composition according to any one of claims 1 to 10; and (b) at least one organic resin.

16. The film of claim 15, wherein the microparticles are embedded in at least one organic resin forming the film.

17. A film according to claim 15 or 16 which is cured.

18. The film of any one of claims 15 to 17, wherein the film is formed by extrusion.

19. The film according to any one of claims 15 to 18, wherein the film does not comprise a barrier layer having low oxygen and moisture permeability adjacent to the film.

20. A nanostructured molded article comprising: (a) a first conductive layer; (b) a second conductive layer; and (c) a nanostructure layer between the first conductive layer and the second conductive layer, wherein the nanostructure layer comprises the composition according to any one of claims 1 to 10.

21. The molded article of claim 20, wherein the nanostructure molded article does not comprise a barrier layer having low oxygen and moisture permeability adjacent to the nanostructure layer.

22. A display device comprising the composition according to any one of claims 1 to 10.

23. The display device of claim 22, wherein the particles are embedded in a matrix forming a film within the display device.

24. The display device of claim 23, wherein the film is disposed on a light guide plate.

25. A display device according to any one of claims 23-24, wherein the display device does not comprise a barrier layer having low oxygen and moisture permeability adjacent to the film.

26. Display backlight unit (BLU), comprising: (a) at least one primary light source emitting primary light; (b) a light guide plate (LGP) optically coupled to the at least one primary light source, whereby the primary light is uniformly transmitted through the LGP; and (c) an extruded film disposed on the LGP, wherein the primary light is uniformly transmitted through the LGP and into the extruded film; wherein the extruded film is not directly physically coupled to the LGP and comprises one or more populations of nanostructures configured to emit secondary light, wherein at least a portion of the primary light is absorbed by the nanostructures and re-emitted by the nanostructures as the secondary light, and wherein the BLU does not comprise a barrier layer.

27. The display BLU of claim 26, wherein the nanostructures comprise nanocrystal cores selected from the group consisting of Si, Ge, Sn, Se, Te, B, C, P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, AgInGaS, and combinations thereof.

28. The display BLU of claim 27, wherein the nanocrystal core comprises InP.

29. The display BLU of claim 27, wherein the nanocrystal core comprises CdSe.

30. The display BLU of any one of claims 27-29, wherein the nanocrystalline core comprises at least one shell.

31. The display BLU of claim 30, wherein the at least one shell is ZnSe.

32. The display BLU of claim 30, wherein the at least one shell is ZnS.

33. The display BLU of claim 27, wherein the nanostructures comprise silver, indium, gallium, and sulfur (AIGS).

34. The display BLU of any of claims 26-33, wherein the extruded film comprises at least one organic resin.

35. The display BLU of claim 34, wherein the at least one organic resin is poly(methyl methacrylate) (PMMA), polyethylene terephthalate (PET), or a combination thereof.

36. The display BLU of any one of claims 26-35, wherein the one or more populations of nanostructures are encapsulated by an inorganic material.

37. The display BLU of claim 36, wherein the inorganic material comprises silicon dioxide particles.